A high-strength, low-gassing inorganic binder and its preparation method and use
By optimizing the components and processes of inorganic binders, various problems in the casting process of traditional inorganic and organic binders are solved, and casting effects with high strength, low gas generation and low pollution are achieved. They are suitable for large, complex and thin Green casting of wall aluminum alloy castings.
Patent Information
- Application Number
- CN202210652037.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-09
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-06-09
AI Technical Summary
Existing water glass inorganic binders have long curing time, low room temperature strength, poor crackability and easy moisture absorption, resulting in a decrease in bonding ability. Organic binders such as phenolic resin and phenolic urea resin are prone to chemical reactions at the casting/casting interface. Reaction, gas volatility is high, severe looseness is produced, subcutaneous pores and irritating smell is large.
By combining the selection of components and contents in the inorganic binder with the mixing hardening process, the casting/casting interface gas reaction during alloy melt casting is produced by short hardening time, high room temperature strength, stable chemical properties, and casting/casting interface gas reaction during alloy melt casting Less inorganic binder.
High-strength, low-cost, low-pollution and short-cycle liquid molding casting of large and complex thin-walled aluminum alloy castings/castings have been achieved, reducing casting defects such as looseness and subcutaneous pores, and reducing the health risks of operators.
Smart Images

Figure CN115007795B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of auxiliary materials for casting of aluminum alloy castings, and in particular relates to a high-strength and low-gassing inorganic binder and a preparation method and application thereof. Background Art
[0002] Aluminum alloy has low density, high specific strength / rigidity, good corrosion resistance, good plasticity, excellent processing performance, good welding performance, excellent electrical conductivity and thermal conductivity, and has been widely used in the field of military equipment. Aluminum alloy can be mainly divided into two categories according to the processing technology: deformed aluminum alloy and cast aluminum alloy. Among them, cast aluminum alloy has good process flow performance and medium load bearing capacity, and has been widely used in the manufacture of products such as missile shells, fuel tank shells, engine accessory casings, engine oil pipelines, automobile engine cylinder blocks, and automobile engine cylinder heads. At present, the existing casting forming process is mainly sand casting. The materials used to make sand molds or sand molds are usually quartz sand and binders. Binders are mainly divided into inorganic binders or organic binders. Inorganic binders are currently mainly water glass binders, and organic binders are mainly phenolic resins, phenol urethane resins or other resin organic binders. When traditional water glass binders are used for sand molds or sand core molding, although serious gas generation will not occur during the casting process, the water glass binder has a long curing time, low room temperature strength, and is very easy to absorb moisture during storage, resulting in a decrease in bonding ability; at the same time, the water glass binder has poor disintegration after casting, making it difficult to clean up after sand removal and unpacking, and the labor intensity of operators is high. Organic binders, especially phenolic resin binders, have a short curing time, high room temperature strength, and stable chemical properties during storage, and will not produce serious quality fluctuations. However, organic binders contain a large amount of C, O and other elements, which are prone to chemical reactions at the casting / mold interface during alloy melt casting, generating a large amount of volatile gases, and are very likely to produce serious looseness, subcutaneous pores and other casting defects at the casting / mold interface; at the same time, organic binders will volatilize when heated and produce a certain amount of harmful gases with a strong irritating smell, which will cause serious damage to the physical and mental health of operators over time.
[0003] With the increasing production tasks in the field of military equipment, a large number of complex structure precision aluminum alloy castings have entered the engineering batch production stage. It is necessary to reduce the quality fluctuations in the batch engineering production process and reduce casting defects such as looseness and subcutaneous pores. At the same time, with the increasingly stringent implementation of environmental protection policies, higher environmental protection technical indicators are required for traditional manufacturing industries, especially high-pollution manufacturing industries such as casting. It is necessary to strictly control the emission of wastewater, waste gas and waste smoke in the casting production process. At the same time, for large and complex structure precision aluminum alloy castings, it is also urgent to solve the process preparation problems of high inner cavity size accuracy, high mechanical performance index requirements, and high metallurgical quality requirements. Summary of the invention
[0004] In order to solve the problems that the existing water glass inorganic binder has a long curing time, low strength at room temperature, poor disintegration and easy moisture absorption during storage resulting in decreased bonding ability, and organic binders such as phenolic resin and phenol urethane resin are prone to chemical reaction at the casting / mold interface during casting, large gas volatilization, severe looseness, subcutaneous pores and strong irritating smell, the present invention provides a high-strength and low-gassing inorganic binder, a preparation method and use thereof. By selecting and matching the components and contents of the inorganic binder and combining it with the mixing and hardening process, a casting core with short hardening time, high room temperature strength, stable chemical properties, less gas reaction at the casting / mold interface during alloy melt casting, and no large amount of gas will be volatilized due to the violent chemical reaction at the casting / mold interface. At the same time, the core has good high-temperature dispersibility, no irritating odor volatilization during the molding and casting process, and a casting core with low volatile gas content can achieve high-strength, low-cost, low-pollution and short-cycle liquid molding casting of large and complex thin-walled aluminum alloy castings / molds. It has broad market application prospects and significant economic benefits, and can achieve green casting of complex thin-walled aluminum alloy castings / molds for military equipment.
[0005] The object of the present invention is achieved through the following technical solutions:
[0006] An inorganic binder, comprising the following components in mass fractions:
[0007] The alkali metal component is 25% to 28%, the preservative component is 4% to 5%, the curing agent component is 30% to 32%, the mixed acid component is 16% to 18%, the modifier component is 5.5% to 7.0%, the sustained-release agent component is 4.5% to 5.5%, and the balance is deionized water.
[0008] According to an embodiment of the present invention, the inorganic binder is used for preparing a casting core.
[0009] According to an embodiment of the present invention, the sum of the mass fractions of the components in the inorganic binder is 100%.
[0010] According to an embodiment of the present invention, the alkali metal component includes sodium silicate, lithium silicate, aluminum phosphate, sodium hydroxide and aluminum hydroxide; preferably, the alkali metal component is composed of sodium silicate, lithium silicate, aluminum phosphate, sodium hydroxide and aluminum hydroxide. The silicates in the alkali metal component react with CO2 in the air under an alkaline environment to form silicate sol, which forms inorganic silicon oxygen chain network macromolecules as the water evaporates and dehydrates, which plays a reinforcing role and can improve the strength of the casting core.
[0011] According to an embodiment of the present invention, the preservative component includes potassium sorbate, sorbic acid, sodium benzoate and calcium propionate; preferably, the preservative component consists of potassium sorbate, sorbic acid, sodium benzoate and calcium propionate. The introduction of the preservative component can prevent bacteria or fungi in the air from breeding in the inorganic binder, deteriorating the use effect of the inorganic binder, and extending the service life of the inorganic binder.
[0012] According to an embodiment of the present invention, the curing agent component includes aluminum oxide, magnesium oxide, zinc oxide, copper oxide, titanium oxide and graphite; preferably, the curing agent component consists of aluminum oxide, magnesium oxide, zinc oxide, copper oxide, titanium oxide and graphite. The introduction of the curing agent component can increase the concentration of mineral ions in the inorganic binder solution and improve the hardening effect of the inorganic binder.
[0013] According to an embodiment of the present invention, the mixed acid component includes silicic acid, phosphoric acid and boric acid; preferably, the mixed acid component consists of silicic acid, phosphoric acid and boric acid. The introduction of the mixed acid component can chemically react with the alkali metal component to form a large amount of silicates in the inorganic binder solution, thereby improving the hardening effect of the inorganic binder.
[0014] According to an embodiment of the present invention, the modifier component includes sodium tripolyborate, potassium disilicate and polyvinyl alcohol; preferably, the modifier component consists of sodium tripolyborate, potassium disilicate and polyvinyl alcohol. The introduction of the modifier component can improve the flow viscosity of the inorganic binder and improve the coating performance of the inorganic binder.
[0015] According to an embodiment of the present invention, the sustained-release agent component is composed of dextrin, silicon dioxide, alginate, hydroxymethyl cellulose and sodium polyacrylate; preferably, the sustained-release agent component is composed of dextrin, silicon dioxide, alginate, hydroxymethyl cellulose and sodium polyacrylate. The introduction of the sustained-release agent component can improve the suspension performance of the inorganic binder solution and prolong the sedimentation time of the inorganic binder solution.
[0016] According to an embodiment of the present invention, the mass percentage of each component in the alkali metal component is:
[0017] Sodium silicate 26%-28% (such as 26%, 26.5%, 27%, 27.5%, 28%), lithium silicate 22%-24% (such as 22%, 22.5%, 23%, 23.5%, 24%), aluminum phosphate 25.5%-27.0% (such as 25.5%, 26%, 26.5%, 27%), sodium hydroxide 7.5%-9% (such as 7.5%, 8%, 8.5%, 9%), and the balance is aluminum hydroxide.
[0018] According to an embodiment of the present invention, the sum of the mass percentages of the various components in the alkali metal component is 100%.
[0019] According to an embodiment of the present invention, the mass percentage of each component in the preservative component is:
[0020] Potassium sorbate 24%-27% (e.g. 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%), sorbic acid 14%-18% (e.g. 14%, 15%, 16%, 17%, 18%), sodium benzoate 20%-24% (e.g. 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%), and the balance is calcium propionate.
[0021] According to an embodiment of the present invention, the sum of the mass percentages of the components in the preservative component is 100%.
[0022] According to an embodiment of the present invention, the mass percentage of each component in the curing agent component is:
[0023] Aluminum oxide 24% ~ 28% (such as 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%), magnesium oxide 12% ~ 14% (such as 12%, 12.5%, 13%, 13.5%, 14%), zinc oxide 8% ~ 12% (such as 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%), copper oxide 16% ~ 20% (such as 16%, 17%, 18%, 19%, 20%), titanium oxide 10% ~ 12% (such as 10%, 10.5%, 11%, 11.5%, 12%), and the balance is graphite.
[0024] According to an embodiment of the present invention, the sum of the mass percentages of the components in the curing agent component is 100%.
[0025] According to an embodiment of the present invention, the mass percentage of each component in the mixed acid component is:
[0026] Silicic acid 32%-35% (such as 32%, 33%, 34%, 35%), phosphoric acid 36%-40% (such as 36%, 37%, 38%, 39%, 40%), and the balance is boric acid.
[0027] According to an embodiment of the present invention, the sum of the mass percentages of the components in the mixed acid component is 100%.
[0028] According to an embodiment of the present invention, the mass percentage of each component in the modifier component is:
[0029] Sodium tripolyborate 40% to 45% (e.g., 40%, 41%, 42%, 43%, 44%, 45%), potassium hydrogen disilicate 45% to 48% (e.g., 45%, 46%, 47%, 48%), and the balance is polyvinyl alcohol.
[0030] According to an embodiment of the present invention, the sum of the mass percentages of the various components in the modifier component is 100%.
[0031] According to an embodiment of the present invention, the mass percentage of each component in the sustained-release agent component is:
[0032] Dextrin 40%-42% (such as 40%, 40.5%, 41%, 41.5%, 42%), silicon dioxide 20%-24% (such as 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%), alginate 10%-12% (such as 10%, 10.5%, 11%, 11.5%, 12%), hydroxymethyl cellulose 6%-8% (such as 6%, 6.5%, 7%, 7.5%, 8%), and the balance is sodium polyacrylate.
[0033] According to an embodiment of the present invention, the sum of the mass percentages of the components in the sustained-release agent component is 100%.
[0034] According to an embodiment of the present invention, the inorganic binder is a colorless, odorless, transparent, high-strength, low-gassing inorganic binder.
[0035] According to an embodiment of the present invention, the viscosity of the inorganic binder is 60 to 100 mPa·s.
[0036] According to an embodiment of the present invention, the high strength means that the casting core prepared by the inorganic binder has the characteristic of high strength, and the low gas evolution means that the casting core prepared by the inorganic binder has the characteristic of low gas evolution.
[0037] The present invention also provides a method for preparing the above-mentioned inorganic binder, which comprises the following steps:
[0038] The inorganic binder is prepared by mixing an alkali metal component, a preservative component, a curing agent component, a mixed acid component, a modifier component, a slow-release agent component and deionized water.
[0039] According to an embodiment of the present invention, the method specifically comprises the following steps:
[0040] (1) adding the alkali metal component, the mixed acid component and deionized water into the reaction kettle by using a vacuum pump, starting the agitator and the heater, slowly raising the temperature to 120° C. to 150° C., and keeping the temperature and stirring for 40 min to 60 min;
[0041] (2) Add the curing agent component while the reaction kettle is continuously stirred, continue heating to 180°C to 200°C, and keep stirring for 30min to 45min;
[0042] (3) Lower the temperature of the reactor to 100°C to 120°C, add the modifier component and the preservative component, and stir for 40min to 60min while keeping the temperature.
[0043] (4) lowering the temperature of the reactor to 60°C to 80°C, stirring continuously until the solution in the reactor becomes transparent, adding the sustained-release agent component, and keeping the temperature and stirring for 25min to 40min;
[0044] (5) Turn off the heater and continue stirring until the solution in the reaction kettle cools to room temperature, then turn off the stirrer to obtain an inorganic binder.
[0045] The present invention also provides application of the inorganic binder for preparing a casting core.
[0046] The present invention also provides a method for preparing a casting core, the method comprising the following steps:
[0047] Mixing the molding sand with the inorganic binder, prefabricating the core, and curing to prepare the casting core; or
[0048] The molding sand is mixed with an inorganic binder to prefabricate a core, which is then heated and purged with gas to prepare the casting core.
[0049] According to an embodiment of the present invention, the molding sand is quartz sand or ceramic sand.
[0050] According to an embodiment of the present invention, the mass ratio of the molding sand to the inorganic binder is 100:2.4-3.2, for example, 100:2.4, 100:2.5, 100:2.6, 100:2.7, 100:2.8, 100:2.9, 100:3.0, 100:3.1, 100:3.2.
[0051] According to an embodiment of the present invention, modeling sand and an inorganic binder are mixed in a sand mixer at room temperature.
[0052] According to an embodiment of the present invention, a core is prefabricated by using a core shooting machine.
[0053] According to an embodiment of the present invention, the curing temperature is 20°C to 40°C, and the curing time is 5min to 40min. After curing, a casting core with a gas evolution of ≤5ml / g, a VOC emission of ≤4ppm, a tensile strength of ≥1.8MPa, and a bending strength of ≥3.5MPa can be obtained.
[0054] According to an embodiment of the present invention, the heating temperature is 140°C to 180°C, the heating time is 2min to 8min, the gas is a mixture of compressed air and CO2, the volume ratio of compressed air to CO2 gas is 1:1.5 to 2.0, the gas purge time is 2min to 4min, and after heating and gas purge, a casting core with a gas emission of ≤3ml / g, a VOC emission of ≤2ppm, a tensile strength of ≥3.0MPa, and a bending strength of ≥6.0MPa can be obtained.
[0055] Beneficial effects of the present invention:
[0056] The present invention provides a high-strength, low-gassing inorganic binder and its preparation method and use. The present invention combines the addition and content selection of alkali metal components, preservative components, curing agent components, mixed acid components, modifier components, and sustained-release agent components with a mixing and hardening process to manufacture casting cores (i.e., sand molds and sand cores) that meet the liquid molding of large, complex, thin-walled, integral precision aluminum alloy castings / molds. Compared with traditional water glass inorganic binders, the casting cores of the present invention after mixing and hardening have stable chemical properties, high room temperature strength, and good disintegration properties. When stored in the air, it is not easy to have the problem of a significant decrease in bonding performance due to moisture absorption; compared with organic resin binders such as phenolic resins and phenol urethane resins, the casting cores of the present invention after mixing and hardening have high room temperature strength, no volatile gas is generated during the molding and casting process, and the manufacturing cost is low, which can achieve green casting of large, complex, thin-walled, integral precision aluminum alloy castings / molds.
[0057] The room temperature strength of the casting core of the present invention is high. When it is used to manufacture an integral or segmented core, the dimensional accuracy of the inner cavity of the casting / mold can be significantly improved. The dimensional tolerance of the casting can be improved by 2 levels, reaching CT6 to CT8, and the surface finish of the inner cavity of the casting is improved by more than 2 times, and the surface roughness reaches 3.2 μm to 12.5 μm. The casting core of the present invention does not generate volatile gas when heated during the molding and casting process, and no violent chemical reaction occurs at the casting / mold interface, so it can greatly reduce casting defects such as looseness and subcutaneous pores, and the density of the casting can be significantly improved. The average tensile strength of the casting after heat treatment can be increased by more than 10 MPa, the yield strength can be increased by more than 12 MPa, and a better elongation after fracture can be obtained, and the qualified rate of aluminum alloy precision castings is greatly improved, and the green casting of large-scale complex thin-walled integral aluminum alloy precision castings is truly realized. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 It is a schematic diagram of the overall sand core structure of the tail section metal shell casting prepared using an inorganic binder in Example 2.
[0059] Figure 2It is a schematic diagram of the structure of the mold for preparing a casting core using an inorganic binder in Example 3.
[0060] Figure markings: ① core shooting machine sand shooting port; ② mold upper plate heater; ③ mold cavity; ④ casting core; ⑤ mold lower plate heater; ⑥ mold metal mold support; ⑦ CO2 gas blowing inlet; ⑧ CO2 gas blowing outlet. DETAILED DESCRIPTION
[0061] The present invention will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0062] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.
[0063] The adhesive viscosity mentioned in the following examples refers to the single cylinder rotation viscometer method for determining the viscosity of adhesives in GB / T 2794-2013.
[0064] The mechanical property test of the cured core mentioned in the following embodiments is carried out using the YXQY-Ⅱ Intelligent Sand Strength Tester produced by Jinan Yongce Industrial Equipment Co., Ltd.
[0065] Embodiment 1:
[0066] The present embodiment provides a high-strength, low-gassing inorganic binder and a preparation method thereof. The high-strength, low-gassing inorganic binder includes the following components in mass fractions: 26.5% alkali metal component, 4.5% preservative component, 31% curing agent component, 17% mixed acid component, 6.5% modifier component, 5.0% sustained-release agent component, and the balance is deionized water.
[0067] The alkali metal component is composed of sodium silicate, lithium silicate, aluminum phosphate, sodium hydroxide and aluminum hydroxide, the preservative component is composed of potassium sorbate, sorbic acid, sodium benzoate and calcium propionate, the curing agent component is composed of aluminum oxide, magnesium oxide, zinc oxide, copper oxide, titanium oxide and graphite, the mixed acid component is composed of silicic acid, phosphoric acid and boric acid, the modifier component is composed of sodium trimerborate, potassium disilicate and polyvinyl alcohol, and the sustained-release agent component is composed of dextrin, silicon dioxide, alginate, hydroxymethyl cellulose and sodium polyacrylate.
[0068] The mass ratio of each component in the alkali metal component is 27% sodium silicate, 23% lithium silicate, 26.5% aluminum phosphate, 8.5% sodium hydroxide, and the balance is aluminum hydroxide. The mass ratio of each component in the preservative component is 25.5% potassium sorbate, 16% sorbic acid, 22% sodium benzoate, and the balance is calcium propionate. The mass ratio of each component in the curing agent component is 26% aluminum oxide, 13% magnesium oxide, 10% zinc oxide, 18% copper oxide, 11% titanium oxide, and the balance is graphite. The mass ratio of each component in the mixed acid component is 33.5% silica, 38% phosphoric acid, and the balance is boric acid. The mass ratio of each component in the modifier component is 42.5% sodium tripolyborate, 46.5% potassium hydrogen disilicate, and the balance is polyvinyl alcohol. The mass ratio of each component in the sustained-release agent component is 41% dextrin, 22% silicon dioxide, 11% alginate, 7% hydroxymethyl cellulose, and the balance is sodium polyacrylate.
[0069] The preparation method steps are as follows:
[0070] (1) Add the alkali metal component, the mixed acid component and deionized water into the reactor using a vacuum pump, start the stirrer and the heater, slowly raise the temperature to 135° C., and keep stirring for 50 minutes;
[0071] (2) Add the curing agent component while the reactor is continuously stirred, continue heating to 190°C, and keep stirring for 37 minutes;
[0072] (3) Lower the temperature of the reactor to 110°C, add the modifier component and the preservative component, and stir for 50 minutes while keeping warm;
[0073] (4) Lower the temperature of the reactor to 70°C, continue stirring until the solution in the reactor becomes transparent, add the sustained-release agent component, and keep stirring for 33 minutes;
[0074] (5) Turn off the heater and continue stirring until the solution in the reactor cools to room temperature, turn off the agitator, open the reactor valve for testing and packaging, and a colorless, odorless, transparent, high-strength, low-gassing inorganic binder can be obtained.
[0075] After mixing quartz sand with the above-mentioned inorganic binder in a sand mixer at room temperature in a mass ratio of 100:3.0, a core is shot out using a core shooter and cured at room temperature for 35 minutes to obtain a casting core (i.e., a sand mold and sand core) with a gas emission of 4 ml / g and a VOC emission of 3 ppm.
[0076] Table 1 Viscosity of the inorganic binder of Example 1 and mechanical properties test results of the sand mold and sand core after curing
[0077]
[0078] Table 2 Comparison results of aluminum alloy castings cast by core casting using the inorganic binder of Example 1 and the inorganic binder of water glass
[0079] Binder type Casting Dimension Tolerance Casting finish Casting surface roughness Example 1 Binder CT7 ▽4 12.5μm Water glass adhesive CT9 ▽1 50μm
[0080] The room temperature strength of the sand core or sand mold after mixing and hardening in Example 1 is high, no volatile gas is generated during the molding and casting process, no violent chemical reaction occurs at the casting / casting interface, and casting defects such as looseness and subcutaneous pores can be greatly reduced. The manufacturing cost is low, and green casting of large, complex, thin-walled integral aluminum alloy precision castings can be achieved. Specifically, the dimensional tolerance of the aluminum alloy casting cast by the casting core prepared by the inorganic binder of Example 1 reaches CT7 level, and the surface roughness of the inner cavity of the casting reaches 12.5μm.
[0081] Embodiment 2:
[0082] The present embodiment provides a high-strength, low-gassing inorganic binder and a preparation method thereof. The high-strength, low-gassing inorganic binder includes the following components in mass fractions: 28% alkali metal component, 5% preservative component, 32% curing agent component, 18% mixed acid component, 7.0% modifier component, 5.5% sustained-release agent component, and the balance is deionized water.
[0083] The alkali metal component is composed of sodium silicate, lithium silicate, aluminum phosphate, sodium hydroxide and aluminum hydroxide, the preservative component is composed of potassium sorbate, sorbic acid, sodium benzoate and calcium propionate, the curing agent component is composed of aluminum oxide, magnesium oxide, zinc oxide, copper oxide, titanium oxide and graphite, the mixed acid component is composed of silicic acid, phosphoric acid and boric acid, the modifier component is composed of sodium trimerborate, potassium disilicate and polyvinyl alcohol, and the sustained-release agent component is composed of dextrin, silicon dioxide, alginate, hydroxymethyl cellulose and sodium polyacrylate.
[0084] The mass ratio of each component in the alkali metal component is 28% sodium silicate, 24% lithium silicate, 27.0% aluminum phosphate, 9% sodium hydroxide, and the balance is aluminum hydroxide. The mass ratio of each component in the antiseptic component is 27% potassium sorbate, 18% sorbic acid, 24% sodium benzoate, and the balance is calcium propionate. The mass ratio of each component in the curing agent component is 28% aluminum oxide, 14% magnesium oxide, 12% zinc oxide, 20% copper oxide, 12% titanium oxide, and the balance is graphite. The mass ratio of each component in the mixed acid component is 35% silica, 40% phosphoric acid, and the balance is boric acid. The mass ratio of each component in the modifier component is 45% sodium tripolyborate, 48% potassium disilicate, and the balance is polyvinyl alcohol. The mass ratio of each component in the sustained-release agent component is 42% dextrin, 24% silicon dioxide, 12% alginate, 8% hydroxymethyl cellulose, and the balance is sodium polyacrylate.
[0085] The preparation method steps are as follows:
[0086] (1) Add the alkali metal component, the mixed acid component and deionized water into the reactor using a vacuum pump, start the stirrer and the heater, slowly raise the temperature to 150° C., and keep stirring for 60 minutes;
[0087] (2) Add the curing agent component while the reactor is continuously stirred, continue heating to 200°C, and keep stirring for 45 minutes;
[0088] (3) Lower the temperature of the reactor to 120°C, add the modifier component and the preservative component, and keep stirring for 60 minutes;
[0089] (4) Lower the temperature of the reactor to 80°C, continue stirring until the solution in the reactor becomes transparent, add the sustained-release agent component, and keep stirring for 40 minutes;
[0090] (5) Turn off the heater and continue stirring until the solution in the reactor cools to room temperature, turn off the agitator, open the reactor valve for testing and packaging, and a colorless, odorless, transparent, high-strength, low-gassing inorganic binder can be obtained.
[0091] After mixing quartz sand with the above-mentioned inorganic binder in a sand mixer at room temperature in a mass ratio of 100:3.0, a core is shot out using a core shooter and cured at room temperature for 40 minutes to obtain a casting core (i.e., a sand mold and sand core) with a gas emission of 3.8 ml / g and a VOC emission of 3.2 ppm.
[0092] Table 3 Viscosity of the inorganic binder of Example 2 and mechanical properties test results of the sand mold and sand core after curing
[0093]
[0094] Table 4 Comparison results of core-cast aluminum alloy castings prepared with the inorganic binder of Example 2 and the phenolic resin binder
[0095] Binder type Casting Dimension Tolerance Casting finish Casting surface roughness Example 2 Binder CT6 ▽5 6.3μm Phenolic resin binder CT10 ▽2 25μm
[0096] The room temperature strength of the sand core or sand mold after mixing and hardening in Example 2 is high, no volatile gas is generated during the molding and casting process, no violent chemical reaction occurs at the casting / casting interface, and casting defects such as looseness and subcutaneous pores can be greatly reduced. The manufacturing cost is low, and green casting of large, complex, thin-walled integral aluminum alloy precision castings can be achieved. Specifically, the dimensional tolerance of the aluminum alloy casting cast by the casting core prepared by the inorganic binder of Example 2 reaches CT6 level, and the surface roughness of the inner cavity of the casting reaches 6.3μm.
[0097] Embodiment 3:
[0098] The present embodiment provides a high-strength, low-gassing inorganic binder and a preparation method thereof. The high-strength, low-gassing inorganic binder includes the following components in mass fractions: 25% alkali metal component, 4% anti-corrosion component, 30% curing agent component, 16% mixed acid component, 5.5% modifier component, 4.5% sustained-release agent component, and the balance is deionized water.
[0099] The alkali metal component is composed of sodium silicate, lithium silicate, aluminum phosphate, sodium hydroxide and aluminum hydroxide, the preservative component is composed of potassium sorbate, sorbic acid, sodium benzoate and calcium propionate, the curing agent component is composed of aluminum oxide, magnesium oxide, zinc oxide, copper oxide, titanium oxide and graphite, the mixed acid component is composed of silicic acid, phosphoric acid and boric acid, the modifier component is composed of sodium trimerborate, potassium disilicate and polyvinyl alcohol, and the sustained-release agent component is composed of dextrin, silicon dioxide, alginate, hydroxymethyl cellulose and sodium polyacrylate.
[0100] The mass ratio of each component in the alkali metal component is 26% sodium silicate, 22% lithium silicate, 25.5% aluminum phosphate, 7.5% sodium hydroxide, and the balance is aluminum hydroxide. The mass ratio of each component in the preservative component is 24% potassium sorbate, 14% sorbic acid, 20% sodium benzoate, and the balance is calcium propionate. The mass ratio of each component in the curing agent component is 24% aluminum oxide, 12% magnesium oxide, 9% zinc oxide, 16% copper oxide, 10% titanium oxide, and the balance is graphite. The mass ratio of each component in the mixed acid component is 32% silica, 36% phosphoric acid, and the balance is boric acid. The mass ratio of each component in the modifier component is 40% sodium tripolyborate, 45% potassium disilicate, and the balance is polyvinyl alcohol. The mass ratio of each component in the sustained-release agent component is 40% dextrin, 20% silicon dioxide, 10% alginate, 6% hydroxymethyl cellulose, and the balance is sodium polyacrylate.
[0101] The preparation method steps are as follows:
[0102] (1) Add the alkali metal component, the mixed acid component and deionized water into the reactor using a vacuum pump, start the stirrer and the heater, slowly raise the temperature to 120° C., and keep stirring for 40 minutes;
[0103] (2) Add the curing agent component while the reactor is continuously stirred, continue heating to 180°C, and keep stirring for 30 minutes;
[0104] (3) Lower the temperature of the reactor to 100°C, add the modifier component and the preservative component, and stir for 40 minutes while keeping the temperature.
[0105] (4) Lower the temperature of the reactor to 60°C, continue stirring until the solution in the reactor becomes transparent, add the sustained-release agent component, and keep stirring for 25 minutes;
[0106] (5) Turn off the heater and continue stirring until the solution in the reactor cools to room temperature, turn off the agitator, open the reactor valve for testing and packaging, and a colorless, odorless, transparent, high-strength, low-gassing inorganic binder can be obtained.
[0107] After mixing quartz sand and the above-mentioned inorganic binder in a sand mixer at room temperature in a mass ratio of 100:3.0, a core is shot using a core shooter. The mold is then heated to 160°C and blown with compressed air + CO2 gas for 3 minutes to obtain a casting core (i.e., sand mold and sand core) with a gas emission of 2.2 ml / g and a VOC emission of 1.6 ppm.
[0108] Figure 2 The schematic diagram is a structural diagram of a mold for preparing a casting core using an inorganic binder in Example 3. Specifically, the preparation steps are as follows: a mold is placed directly above the mold metal mold support 6, quartz sand and an inorganic binder are mixed, and then the mixed sand is injected into the mold cavity 3 through the core shooting machine sand shooting port 1. The mold upper plate heater 2 and the mold lower plate heater 5 are started to heat the sand inside the mold cavity 3; at the same time, the CO2 gas blowing inlet 7 and the CO2 gas blowing outlet 8 are opened to introduce CO2 gas into the mold cavity 3. Under the action of the mold upper plate heater 2 and the mold lower plate heater 5, the CO2 gas undergoes a hardening chemical reaction with the inorganic binder in the sand, and a casting core 4 with high dimensional accuracy and good surface finish is quickly prepared for the molding and casting of aluminum alloy castings.
[0109] Table 5 Viscosity of the inorganic binder of Example 3 and mechanical properties test results of the sand mold and sand core after heated gas purging
[0110]
[0111] Comparative Example 1
[0112] The other operations were the same as those in Example 1, except that the inorganic binder in Example 1 was replaced by a water glass binder of equal mass (purchased from Shandong Xinbaihe Chemical Technology Co., Ltd.).
[0113] Table 6 Sand mold strength test results prepared by the inorganic binder of Example 1 and the water glass binder of Comparative Example 1
[0114]
[0115] Comparative Example 2
[0116] The other operations were the same as those in Example 1, except that the inorganic binder in Example 1 was replaced by an equal mass of phenolic resin organic binder (purchased from Jinan Shengquan Group Co., Ltd.).
[0117] Table 7 Sand mold strength and gas generation test results prepared by the inorganic binder of Example 1 and the phenolic resin binder of Comparative Example 2
[0118]
[0119] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An inorganic binder, characterized in that: The inorganic binder is composed of the following components in mass fraction: Alkali metal component 25% to 28%, preservative component 4% to 5%, curing agent component 30% to 32%, mixed acid component 16% to 18%, modifier component 5.5% to 7.0%, sustained-release agent component 4.5% to 5.5%, and the balance is deionized water; The mixed acid component includes silicic acid, phosphoric acid and boric acid; The mass percentage of each component in the mixed acid component is: Silicic acid 32% to 35%, phosphoric acid 36% to 40%, the balance is boric acid; The modifier components include sodium triborate, potassium hydrogen disilicate and polyvinyl alcohol; The mass percentage of each component in the modifier component is: Sodium tripolyborate 40% to 45%, potassium hydrogen disilicate 45% to 48%, and the balance is polyvinyl alcohol; The curing agent component includes aluminum oxide, magnesium oxide, zinc oxide, copper oxide, titanium oxide and graphite; The mass percentage of each component in the curing agent component is: Aluminum oxide 24% to 28%, magnesium oxide 12% to 14%, zinc oxide 8% to 12%, copper oxide 16% to 20%, titanium oxide 10% to 12%, and the balance is graphite; The alkali metal component includes sodium silicate, lithium silicate, aluminum phosphate, sodium hydroxide and aluminum hydroxide; The preservative components include potassium sorbate, sorbic acid, sodium benzoate and calcium propionate; The sustained-release agent components include dextrin, silicon dioxide, alginate, hydroxymethyl cellulose and sodium polyacrylate; The mass percentage of each component in the alkali metal component is: Sodium silicate 26%-28%, lithium silicate 22%-24%, aluminum phosphate 25.5%-27.0%, sodium hydroxide 7.5%-9%, and the balance is aluminum hydroxide; The mass percentage of each component in the preservative component is: Potassium sorbate 24%-27%, sorbic acid 14%-18%, sodium benzoate 20%-24%, the balance is calcium propionate; The mass percentage of each component in the sustained-release agent component is: Dextrin 40%-42%, silicon dioxide 20%-24%, alginate 10%-12%, hydroxymethyl cellulose 6%-8%, and the balance is sodium polyacrylate.
2. The inorganic binder according to claim 1, characterized in that The viscosity of the inorganic binder is 60-100 mPa·s.
3. The method for preparing the inorganic binder according to any one of claims 1 to 2, comprising the following steps: The inorganic binder is prepared by mixing an alkali metal component, a preservative component, a curing agent component, a mixed acid component, a modifier component, a slow-release agent component and deionized water.
4. The preparation method according to claim 3, characterized in that: The method specifically comprises the following steps: (1) adding the alkali metal component, the mixed acid component and deionized water into the reaction kettle by using a vacuum pump, starting the agitator and the heater, slowly raising the temperature to 120° C. to 150° C., and keeping the temperature and stirring for 40 min to 60 min; (2) Add the curing agent component while the reaction kettle is continuously stirred, continue heating to 180°C to 200°C, and keep stirring for 30min to 45min; (3) Lower the temperature of the reactor to 100°C to 120°C, add the modifier component and the preservative component, and stir for 40min to 60min while keeping the temperature. (4) lowering the temperature of the reactor to 60°C to 80°C, stirring continuously until the solution in the reactor becomes transparent, adding the sustained-release agent component, and keeping the temperature and stirring for 25min to 40min; (5) Turn off the heater and continue stirring until the solution in the reaction kettle cools to room temperature, then turn off the stirrer to obtain an inorganic binder.
5. A method for preparing a casting core, characterized in that: The method comprises the following steps: Mixing molding sand with the inorganic binder according to any one of claims 1 to 2, prefabricating a core, and curing to prepare the casting core; or, The molding sand is mixed with the inorganic binder according to any one of claims 1 to 2 to prepare a core, and then heated and gas purged to prepare the casting core.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the molding sand to the inorganic binder is 100:2.4-3.
2.
7. The preparation method according to claim 5, characterized in that: The curing temperature is 20°C to 40°C, the curing time is 5min to 40min, and after curing, a casting core with a gas emission of ≤5ml / g, a VOC emission of ≤4ppm, a tensile strength of ≥1.8MPa, and a bending strength of ≥3.5MPa can be obtained.
8. The preparation method according to claim 5, characterized in that: The heating temperature is 140°C to 180°C, the heating time is 2min to 8min, the gas is a mixture of compressed air and CO2, the volume ratio of compressed air to CO2 gas is 1:1.5 to 2.0, the gas purging time is 2min to 4min, and after heating and gas purging, a casting core with a gas emission of ≤3ml / g, a VOC emission of ≤2ppm, a tensile strength of ≥3.0MPa, and a bending strength of ≥6.0MPa can be obtained.
Citation Information
Patent Citations
Hot core sand inorganic binder and preparing method thereof
CN108405794A
Inorganic binder for casting
CN110000330A